2018
DOI: 10.2147/ijn.s173063
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-enabled materials for hemostatic and anti-infection treatments in orthopedic surgery

Abstract: The hemostatic and anti-infection treatments in the field of orthopedics are always the pivotal yet challenging topics. In the first part of this review, synthesized or naturally derived nanoscale agents and materials for hemostatic treatment in orthopedic surgery are introduced. The hemostatic mechanisms and the safety concerns of these nanotechnology-enabled materials are discussed. Beside the materials to meet hemostatic needs in orthopedic surgery, the need for antimicrobial or anti-infection strategy in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…This strategy is very important because it is less likely to impact bacteria gene machinery, and it may include antibiofilm agents to reduce bacteria adhesion. 15,[67][68][69][70][71] In this sense, the prototype red pepper coat (CSP spin-coated slides) prevented bacterial adhesion, aggregation, accumulation and consequently biofilm establishment. This activity seems to be concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is very important because it is less likely to impact bacteria gene machinery, and it may include antibiofilm agents to reduce bacteria adhesion. 15,[67][68][69][70][71] In this sense, the prototype red pepper coat (CSP spin-coated slides) prevented bacterial adhesion, aggregation, accumulation and consequently biofilm establishment. This activity seems to be concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…A model of self-assembling fibers comprised of nanofabricated chitosan fibers shows hemostatic action possibly due to the cation properties of chitosan and nonspecific cell membrane binding to improve platelet aggregation over traditional chitosan sponge. Mesh structures have achieved hemostasis in a rabbit liver model [39,40]. Another topical hemostatic employed narrow-sized, rapid-swelling cationic hydrogel particlea based on N-(3-aminopropyl) methacrylamide with significant blood loss reduction in a rat liver and tail amputation model [40,41].…”
Section: Synthetic Topical Hemostatic Nanomoleculesmentioning
confidence: 99%
“…Mesh structures have achieved hemostasis in a rabbit liver model [39,40]. Another topical hemostatic employed narrow-sized, rapid-swelling cationic hydrogel particlea based on N-(3-aminopropyl) methacrylamide with significant blood loss reduction in a rat liver and tail amputation model [40,41].…”
Section: Synthetic Topical Hemostatic Nanomoleculesmentioning
confidence: 99%
“…Recently, NP-induced coagulopathy has become a serious concern with several studies reporting an increased risk of cardiovascular disease due to NP-induced thrombotic complications. Different studies have found that NPs can perturb the coagulation system and cause a shift in the hemostatic balance, resulting in serious life-threatening conditions such as deep vein thrombosis (DVT) and disseminated intravascular coagulopathy (DIC) [4]. The exact mechanisms behind such toxicities have not yet been clearly defined, even though some progress has been made on critical factors that drive the adverse effects of NPs on the hemostatic system.…”
Section: Introductionmentioning
confidence: 99%